2023
DOI: 10.1038/s41598-022-26372-y
|View full text |Cite
|
Sign up to set email alerts
|

An efficient annotation method for image recognition of dental instruments

Abstract: To prevent needlestick injury and leftover instruments, and to perform efficient dental treatment, it is important to know the instruments required during dental treatment. Therefore, we will obtain a dataset for image recognition of dental treatment instruments, develop a system for detecting dental treatment instruments during treatment by image recognition, and evaluate the performance of the system to establish a method for detecting instruments during treatment. We created an image recognition dataset usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The classification for PPE protection every parts of worker body, which are head with bump caps, eyes with safety goggles, hearing with ear plugs, breathing with respirators, hand with gloves, foot safety toed shoes, skin coats and body with safety vest. Oka et al [4] presented how to recognize 24 kinds of dental instruments in 1425 images with correctly and operate safely by using a convolution neural network. The average precision rates of the system are 89.7%…”
Section: Safety Purposementioning
confidence: 99%
See 1 more Smart Citation
“…The classification for PPE protection every parts of worker body, which are head with bump caps, eyes with safety goggles, hearing with ear plugs, breathing with respirators, hand with gloves, foot safety toed shoes, skin coats and body with safety vest. Oka et al [4] presented how to recognize 24 kinds of dental instruments in 1425 images with correctly and operate safely by using a convolution neural network. The average precision rates of the system are 89.7%…”
Section: Safety Purposementioning
confidence: 99%
“…Method Tool types Number of Images Precision % Kurnaz [2] Faster RetinaNet 49 2,788 85.00 Oka [4] Yolo V7 24 1,425 80.80 Manici [5] Alex Net 9 4,500 60.00 Stasiak [9] KNN 10 150 85.00 Hernandez [11] Yolo 24 8,000 98.00 This Research ResNet50 110 99,000 99.30…”
Section: Authormentioning
confidence: 99%
“…While this study employed static images as a preliminary step in the development of the DL model for US diagnosis, our ultimate goal is to create a DL model capable of real-time detection of metastatic LNs during live US video examinations. In this study, the YOLO version 7 (YOLOv7) algorithm was used since previous studies have suggested that YOLOv7 provides greater accuracy and requires less computation time [40][41][42][43][44][45]. The salient features of YOLOv7 used in this study are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Provides predesigned freebies to facilitate model fine-tuning and simplifies the addition of modules and the creation of new models, which are characterized by higher detection accuracy, speed, and convenience [40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that YOLOv7 is faster, but lighter YOLO models can achieve real-time tracking. Oka S. et al [26] developed an image recognition system for detecting dental instruments during treatment to prevent injuries and leftover instruments. YOLOv4 and YOLOv7 were used, with mean detection accuracy ranging from 85.3% to 89.7%.…”
mentioning
confidence: 99%